Pedagogical Technologies and Their Practical Implementation in Literature Lessons - Marupova D.D. (Peerian Journals Publishing, 2022)
The article considers the technological aspect of the professional didactic activity of a teacher. In this regard, the pedagogical technologies used in the modern education system are presented, as well as the most effective pedagogical technologies used by the teacher in the pedagogical practice of teaching literary disciplines; attention is paid to the development of a flexible learning model that takes into account various technologies of mastering the material; the task is to create an effective technology for managing the speech-thinking, intellectual and cognitive activity of students in order to form communicative competence
Keywords: innovative pedagogical technologies; professional competence; literary activity; quality of training